Parental COVID-19 vaccine hesitancy for children: vulnerability in an urban hotspot - Nina L. Alfieri; Jennifer D. Kusma; Nia Heard-Garris; Matthew M. Davis; Emily Golbeck; Leonardo Barrera; Michelle L. Macy (BMC, 2021)
Abstract Objective To compare hesitancy toward a future COVID-19 vaccine for children of various sociodemographic groups in a major metropolitan area, and to understand how parents obtain information about COVID-19. Methods Cross-sectional online survey of parents with children < 18 years old in Chicago and Cook County, Illinois, in June 2020. We used logistic regression to determine the odds of parental COVID-19 vaccine hesitancy (VH) for racial/ethnic and socioeconomic groups, controlling for sociodemographic factors and the sources where parents obtain information regarding COVID-19. Results Surveys were received from 1702 parents and 1425 were included in analyses. Overall, 33% of parents reported VH for their child. COVID-19 VH was higher among non-Hispanic Black parents compared with non-Hispanic White parents (Odds Ratio (OR) 2.65, 95% Confidence Interval (CI): (1.99-3.53), parents of publicly insured children compared with privately insured (OR 1.93, (1.53-2.42)) and among lower income groups. Parents receive information about COVID-19 from a variety of sources, and those who report using family, internet and health care providers as information sources (compared to those who don't use each respective source) had lower odds of COVID-19 VH for their children. Conclusions The highest rates of hesitancy toward a future COVID-19 vaccine were found in demographic groups that have been the most severely affected by the pandemic. These groups may require targeted outreach efforts from trusted sources of information in order to promote equitable uptake of a future COVID-19 vaccine.